The Impact of International Integration on the Inequality of Income between Rural and Urban Areas in Vietnam - Nguyễn Thị Thu Hiền; Nguyễn Thị Thanh Huyền; Nguyễn Thị Lệ Hằng; Nguyễn Văn Công (My University, 2020)
The Impact of International Integration on the Inequality of Income between Rural and Urban Areas in Vietnam
Keywords: International Integration; Income Inequality; Rural-Urban